212k views
2 votes
Polynomial long division​

Polynomial long division​-example-1
User Nogard
by
6.0k points

1 Answer

4 votes

You're dividing
2x^3-2x^2+3x-4 (1) by
x+1 (2).


2x^3=2x^2\cdot x, and
2x^2(x+1)=2x^3+2x^2 (3). Subtract this from (1) to get a remainder of


(2x^3-2x^2+3x-4)-(2x^3+2x^2)=-2x^2+3x+4 (4)


-2x^2=-2x\cdot x, and
-2x(x+1)=-2x^2-2x (5). Subtract this from (4) to get a new remainder of


(-2x^2+3x+4)-(-2x^2-2x)=5x+4 (6)


5x=5\cdot x, and
5(x+1)=5x+5 (7). Subtract this from (6) to get a new remainder of


(5x+4)-(5x+5)=-1 (8)


-1 doesn't contain any factors of
x, so we're done and we've shown


(2x^3-2x^2+3x-4)/(x+1)=2x^2+(-2x^2+3x+4)/(x+1)


(2x^3-2x^2+3x-4)/(x+1)=2x^2-2x+(5x+4)/(x+1)


(2x^3-2x^2+3x-4)/(x+1)=2x^2-2x+5-\frac1{x+1}

so that the quotient is
2x^2-2x+5 (9).

Polynomial long division​-example-1
User Xudong Zhang
by
5.3k points